The Study of the Effect of Cognitive-Behavioral Therapy (CBT) on Reducing Methadone Consumption and Increasing Self-Esteem in Drug Addicts - Zakaria Zakariaei1, Seyed Khosro Ghasempouri1, Touraj Assadi2, Ali Asghar Manouchehri3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The purpose of this study is to determine the effectiveness of cognitive behavioral therapy (CBT) in reducing methadone consumption and increasing self-belief in addicted to substance people. This study is in terms of the objective of applied research and from the developmental branch and in terms of nature and method it is a quasi_experimental research. The study population of this study includes all clients of methadone clinic of razi hospital in qaemshahr. The sample consisted of 30 subjects selected through targeted sampling available were divided into control and experimental groups, who referred to methadone clinic at razi hospital in Qaem-shahr during the study period. Data collection tool was a standard and researcher-made questionnaire. Franken’s Methadone Consumption Reduction Questionnaire (2002) and Self-confidence researcher-made questionnaire, which reliability was calculated to be 0.94 and 0.74 respectively, using Cronbach’s Alpha. Spss22 software was used to analysis the research hypotheses and data from the questionnaire. The data analysis method has been descriptive and inferential statistics (Kolmogorov–Smirnov, Levine, T2 and covariance test). The result of this study has been shown that cognitive behavioral therapy (CBT) is effective in reducing the consumption of methadone addicts. Cognitive behavioral therapy (CBT) increases self-belief in addicted people.